Helping farmers escape the poverty trap through sustainable livelihoods - Aditya Alta; Amalina Az Zahra; Azizah Nazzala Fauzi (Center for Indonesian Policy Studies (CIPS), 2023)
The contribution of agriculture to the Indonesian economy is in decline, but the sector still provides employment to a relatively large number of Indonesians. Because of low productivity, poverty has become the main social issue for farmers. Farming is concentrated in rural areas, and so farmers also face challenges that do not affect those living in urban areas. This paper employs the 'sustainable livelihoods approach,' which considers welfare outcomes as the result of interactions between contextual factors, livelihood resources or assets, policies and institutions, and livelihood strategies. Employing this approach to a case study of two villages in Central Java, this paper assesses the extent to which existing policies and programs have addressed the challenges facing rural agricultural workers.
Keywords: 330